Exploring Public Secondary Students’ Classroom Participation in Communicative Language Teaching in Gauriganga Nepal - Upadhyay, Mathura Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
This article explores the factors that affect classroom participation and effective strategies to increase the active involvement of public secondary students' in communicative language classrooms in Gaurganga Nepal. It aims to detect the techniques to increase the active involvement of the learners in classroom discussions. This research was conducted in Gauriganga Municipality, Kailai. I have used phenomenology as a research design within a qualitative framework. This approach stresses the existence of multiple realities, acknowledging that participation is complex, and affected by various factors such as cultural backgrounds, language skills, fear of criticism, lack of content and vocabulary knowledge, classroom size, teaching methods, and materials. Two English language teachers were selected through purposeful sampling. The data were collected through in-depth interviews with these teachers teaching at the secondary level. The results revealed that teachers used various strategies such as communicative language teaching, motivating students, and learner-centered techniques like role play, group work, simulations, games, and information communication technology which were crucial for engaging students in classroom activities. In short, developing self-confidence in the learners by creating a learner-friendly environment and respecting varied abilities became an effective strategy for engaging students in classroom activities.